Influence of Brake Pad Properties to Braking Characteristics - Viderščak, Dalibor; Schauperl, Zdravko; Ormuž, Krunoslav; Šolić, Sanja; Nikšić, Mladen; Milčić, Diana; Ormuž, Pavao (Promet - Traffic&Transportation, 2022)
In this research, field and laboratory testing of three commercially available brake pads with the lowest, mid-dle, and highest price were performed. Complex field testing, where brake pads were tested in real extreme conditions on a loaded van vehicle and laboratory tests were performed. The field testing intended to investigate the temperatures that occur during the braking process and to determine the stopping distance, deceleration, and stopping time separately on the type of brake pads. Labo-ratory tests included the determination of the friction co-efficient according to ASTM G77, the structure of brake pad surfaces before and after the testing, and quantitative chemical analysis of brake pads. The aim of this study was to determine the influence of brake pad temperature on braking time depending on their purchase prices. The obtained results show a significant difference between the temperature, friction coefficient, chemical composi-tion, and braking time of the brake pads and their price.